2011
DOI: 10.4049/jimmunol.1002006
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Talk between Programmed Death-1 and Suppressor of Cytokine Signaling-1 in Inhibition of IL-12 Production by Monocytes/Macrophages in Hepatitis C Virus Infection

Abstract: Hepatitis C virus (HCV) dysregulates innate immune responses and induces persistent viral infection. We previously demonstrated that HCV core protein impairs IL-12 expression by monocytes/macrophages (M/MΦs) through interaction with a complement receptor gC1qR. Because HCV core-mediated lymphocyte dysregulation occurs through the negative immunomodulators programmed death-1 (PD-1) and suppressor of cytokine signaling-1 (SOCS-1), the aim of this study was to examine their role in HCV core-mediated IL-12 suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 45 publications
4
85
0
Order By: Relevance
“…These results are in agreement with our previous observations that another negative signaling molecule, T cell immunoglobulin and mucin domain protein 3 (Tim-3), is upregulated on NK cells to dampen their functions, with inhibited activation (CD69), proliferation (Ki69), degranulation (CD107a), and killing activity (granzyme B) following HCV infection (data not shown). This in turn interplays with monocytes and T cells (including Th17 and Foxp3 ϩ Tregs) in immune dysregulation that contribute to viral persistence (42)(43)(48)(49). This also supports the notion that HCV may utilize KLRG1-an intrinsic mercenary of cell feedback regulation-for the purpose of virus persistence and thus facilitate chronic infection.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…These results are in agreement with our previous observations that another negative signaling molecule, T cell immunoglobulin and mucin domain protein 3 (Tim-3), is upregulated on NK cells to dampen their functions, with inhibited activation (CD69), proliferation (Ki69), degranulation (CD107a), and killing activity (granzyme B) following HCV infection (data not shown). This in turn interplays with monocytes and T cells (including Th17 and Foxp3 ϩ Tregs) in immune dysregulation that contribute to viral persistence (42)(43)(48)(49). This also supports the notion that HCV may utilize KLRG1-an intrinsic mercenary of cell feedback regulation-for the purpose of virus persistence and thus facilitate chronic infection.…”
Section: Discussionsupporting
confidence: 59%
“…Additionally, the driving force for KLRG1 upregulation during HCV infection remains to be determined. To further elucidate the role of HCV in regulation of KLRG1 expression, we employed a newly established cell culture system by transfecting Huh-7 hepatocytes with the HCV JFH-1 strain in vitro to mimic the in vivo setting of early HCV infection (42,43). To this end, PBMCs or purified NKs from HS were cocultured with HCV-transfected or untransfected Huh-7 hepatocytes for 48 h, followed by flow cytometric analysis for KLRG1 expression and NK functions.…”
Section: Cd56mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, multiorgan inflammation and premature death are observed in transgenic mice overexpressing the IL-23 p19 subunit (18). Previous studies have found that IL-12 family members, such as IL-12 and IL-27, are involved in chronic inflammation and liver damage from HBV and hepatitis C virus infections (19)(20)(21)(22). However, the regulatory mechanism of IL-23 in chronic HBV infection remains largely unknown.…”
Section: H Epatitis B Virus (Hbv) Infection Is One Of the Leadingmentioning
confidence: 98%